Russian “duboglot” in Charms and Dialectal Vocabulary (towards Investigation of Mytho-Poetic Motivation of Words) - Agapkina, Tatyana A.; Berezovich, Elena L. (Slověne, 2020)
The article considers the word duboglot, which functions in the Russian dialects (mainly South Russian) in the meanings of ‘strong dry cough, usually accompanied by a sore throat,’ ‘angina.’ Semantic and motivational reconstruction of this word is carried out based on its role in the text. The authors conclude that the word got into the dialect system from the folklore (mainly from the charms), where it refers to diseases related to inflammation of the oral cavity, pharynx and lower respiratory tract, and accompanied by a strong cough, pain. It is established that most often the word appeared in the texts as a part of the formula “X (a tree), take your Y (duboglot), otherwise I will eat you / swallow you,” which is initially addressed to an oak tree as a convenient “recipient” of diseases that are expelled from the speaker’s space. The authors suggest that the word duboglot is “induced” by the logic of unfolding the text: this is “the oak glot” (glot is the ability to swallow – from the Russian verb glotat’ ‘to swallow’), which should belong to an oak, not a sick person. The word creation within the framework of a spoken construction is supported by the capabilities that are inherent in the language system. Firstly, it is the image of an oak “mouth” (throat), which is formed on the basis of the natural properties and features of oak. This image could be fixed in the internal form of the word itself, which is a controversial issue, but it certainly is seen in the stable compatibility of dub ‘oak’ ↔ duplo ‘hollow’, and at the synchronous level is also supported by the phonetic proximity of these words. The image of a tree, secondly, has another facet: the image of roots of a tree and its crown is projected on the idea of the growth of a tumour (including one in the throat); roots and crown of a tree simultaneously seem to be a “tool” for clearing the throat. Yet another facet of the image is related to how the native speaker sees the properties of a bark: there is a productive model for the Russian language that fixates the connection between the designations of wood (oak) bark and tumours on the human body (including throat tumours); oak bark itself is generally an “archetype” of a bark, hard, rough, stripped from the surface of a tree (which corresponds to “tearing” sensations with a sore throat).